2020
DOI: 10.1007/s00222-020-00967-6
|View full text |Cite
|
Sign up to set email alerts
|

Kazhdan groups have cost 1

Abstract: We prove that every countably infinite group with Kazhdan's property (T) has cost 1, answering a well-known question of Gaboriau. It remains open if they have fixed price 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In [4], it was shown that any group with property (T) has cost 1. This raises the question if a similar theorem can be proved in the combinatorial context.…”
Section: Definition 14 ([1]mentioning
confidence: 99%
“…In [4], it was shown that any group with property (T) has cost 1. This raises the question if a similar theorem can be proved in the combinatorial context.…”
Section: Definition 14 ([1]mentioning
confidence: 99%